Are children's vitamin D levels and BMI associated with antibody titers produced in response to 2014–2015 influenza vaccine?. Issue 7 (3rd July 2017) - Lin, Chyongchiou J.; Martin, Judith M.; Cole, Kelly Stefano; Zimmerman, Richard K.; Susick, Michael; Moehling, Krissy K.; Levine, Min Z.; Spencer, Sarah; Flannery, Brendan; Nowalk, Mary Patricia
ABSTRACT: Background : Vitamin D is an immunomodulating hormone, which has been associated with susceptibility to infectious diseases. Methods : Serum vitamin D levels in 135 children ages 3–17 y were measured at baseline and hemagglutinin influenza antibody titers were measured pre- and 21 d post influenza vaccination with live attenuated influenza vaccine (LAIV) or inactivated influenza vaccine (IIV). Height and weight were derived from the electronic medical record and were used to calculate body mass index (BMI). Results : Thirty-nine percent of children were ages 3–8 years; 75% were black, 34% were obese (BMI ≥ 95 th percentile); vitamin D levels were >20 ng/ml in 55%. In linear regression analyses, post vaccination antibody titers for LAIV B lineages (B Brisbane and B Massachusetts) were significantly higher among those with lower vitamin D levels and among younger participants ( P < 0.05). No associations between vitamin D levels and responses to LAIV A strains (A/H1N1 and A/H3N2) or to any IIV strains or lineages were found. Conclusion : Low vitamin D levels were associated with higher response to LAIV B lineages in the 2014–2015 LAIV, but not related to LAIV A or any IIV strains.